Ecological factors affecting the structure, diversity, and specialisation of caterpillar communities in forest ecosystems - Seifert, Carlo Lutz (Jihočeská univerzita, 2020)
The aim of the thesis was to explore how caterpillar assemblages are spatially, functionally, and taxonomically structured in temperate and tropical forest ecosystems. Firstly, we investigated to what extent caterpillar assemblages are vertically structured in a temperate forest in eastern North America. By using a comprehensive dataset of temperate forest sites across three continents, we further examined if distance metrics derived from plant phylogeny can be used to predict structural changes in caterpillar assemblages among co-occurring plants. We further studied if folivorous caterpillars associated with bamboo in an Ecuadorian montane rainforest can be considered as 'classical' herbivores (sensu stricto). In the last chapter, we introduce and compare plot-based sampling approaches to study interaction networks in forest ecosystems and provide comprehensive guidelines for replication in future studies.
Ecological factors affecting the structure, diversity, and specialisation of caterpillar communities in forest ecosystems
Keywords: caterpillars; forest ecosystems; guilds; insect herbivores; interaction networks; Lepidoptera; specialisation; caterpillars; forest ecosystems; guilds; insect herbivores; interaction networks; Lepidoptera; specialisation